Complete mitochondrial genome of the Tristram's Bunting, Emberiza tristrami (Aves: Passeriformes): The first representative of the family Emberizidae with six boxes in the central conserved domain II of control region. (December 2013) - Kan, Xianzhao; Yuan, Jian; Zhang, Liqin; Li, Xifeng; Yu, Lei; Chen, Lei; Guo, Zhichun; Yang, Jianke
<x xml:space="preserve">Abstract</x> Mitochondrial genome has proven to be a powerful tool for phylogenetic inference, phylogeography, and molecular evolution. In this study, we determined the complete mitochondrial genome of Emberiza tristrami (Passeriformes: Emberizidae) for use in future phylogenetic analyses. This circular mitochondrial genome is 16, 789 bp in length and composed of 13 typical protein-coding genes, 22 transfer RNA genes, 2 ribosomal RNA genes, and 1 putative control region (CR). One extra nucleotide "C" of nad3 is not detected in the mitogenome of E. tristrami. The CR of E. tristrami can be divided into three domains: ETAS (extended termination-associated sequence) domain I (nt 1–431), central conserved domain II (nt 432–847), and CSB (conserved sequence block) domain III (nt 848–1217). Six conserved sequence boxes in the central conserved domain II were identified as boxes F, E, D, C, b, and B.